PENGARUH KONSENTRASI XANTHAN GUM TERHADAP STABILITAS FISIK KRIM VIRGIN COCONUT OIL (VCO) - Beti Pudyastuti; Marchaban Marchaban; Rina Kuswahyuning (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2015)
Abstract: Virgin Coconut Oil (VCO) is a pure oils that is extracted from fresh coconut meat at low temperatures. The formulation of VCO in cream dosage form could retain skin moisture and improve the acceptability. Xanthan gum is one of the emulsifier that used to form oil in water (O/W) cream. The purpose of this research were to determine the effect of xanthan gum concentration to the physical stability of VCO cream. VCO creams were prepared by emulsifying the oil phase and the water phase with the variation of xanthan gum concentration (2.5; 2.7; 2.9; 3.1; 3.3% w/w). Observation of the physical stability of the cream includes organoleptic, emulsion type, droplets size, viscosity, spreadability, adhesion, and ratio of separation volume was conducted until 7th week, and also the freeze-thaw test for three cycles. The results showed that each formulation could produces homogeneous light brown cream with oil in water type. Increasing of xanthan gum concentration would increases viscosity of the cream so that spreadability decreases and adhesion increases during stability study. Ratio of separation volume increased after three cycles of freeze-thaw test. Cream with 3.3% w/w xanthan gum had the optimum physical stability.Keywords : VCO, O/W cream, xanthan gum, physical stability